Identification of microbial inhibitions and mitigation strategies towards cleaner bioconversions of palm oil mill effluent (POME): A review - Yoke, Wang Cheng; Chi, Cheng Chong; Man, Kee Lam; Wai, Hong Leong; Lai, Fatt Chuah; Suzana, Yusup; Setiabudi, H. D.; Tang, Yuanyuan; Jun, Wei Lim (Elsevier, 2021)
Flourishing oil palm agroindustry inevitably produces voluminous pollutant-laden palm oil mill effluent(POME), which often treated by obsolete open ponding. By introducing foreign microbes, POME bio-conversions confer simultaneous valorization and remediation of POME; however, environmental-sensitive microbes are prone to microbial inhibitions, which can upset the bioconversion. Herein, upto eight possible microbial inhibitions of POME bioconversions are identified and detailed after holisticreview of multitudinous bioconversion routes. Potential microbial inhibitions include oil encapsulation,chemical inhibition, physical disruption, strict oxygen preference (O2toxicity/deficiency), extremetemperature (cold/thermal denaturation), extreme pH (acid/alkali toxicity), extreme salinity, and pho-toinactivation. To lessen microbial inhibitions in POME bioconversions, constructive mitigation strategiesare classified into three aspects,viz.substrate aspects (debris removal, supplementation, dilution, pre-treatments,&co-substrates addition), microbial aspects (mixed cultures, immobilization, granulation,&gradual acclimation), and process aspects (thermophilic anaerobic/mesophilic aerobic pairs, continuousoperation, pH control/adjustment, biosludge recycling/entrapment,&additional bioreactor). In authors’opinion, genetically modified microbes (GMM) application in POME bioconversions might be a promisingresearch direction. Aforesaid superbugs can be engineered for efficient bioremediation, rapid prolifera-tion, and high adaptability, which likely resolve all the aforesaid microbial inhibitions via geneticengineering